Partial Activation of Purified Prothrombin: Derivation of Autoprothrombin I with Use of Autoprothrombin C - Seegers, Walter H; Cole, Edmond R; Marciniak, Ewa (Thrombosis and Haemostasis, 1962)
Activation of purified prothrombin with autoprothrombin C in the absence of calcium ions produces autoprothrombin I activity. The solubility, and stability properties of this autoprothrombin I are different from those of autoprothrombin I when obtained by activating prothrombin with calcium ions, platelet factor 3, and Ac-globulin.